If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 26 = 7(5 + -4f) 26 = (5 * 7 + -4f * 7) 26 = (35 + -28f) Solving 26 = 35 + -28f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '28f' to each side of the equation. 26 + 28f = 35 + -28f + 28f Combine like terms: -28f + 28f = 0 26 + 28f = 35 + 0 26 + 28f = 35 Add '-26' to each side of the equation. 26 + -26 + 28f = 35 + -26 Combine like terms: 26 + -26 = 0 0 + 28f = 35 + -26 28f = 35 + -26 Combine like terms: 35 + -26 = 9 28f = 9 Divide each side by '28'. f = 0.3214285714 Simplifying f = 0.3214285714
| n^3+9=9n^2+n | | half(6x-4)=3+-2 | | 2-(3x+18)=6(x-1)+12 | | 7+14x-3=2(x-4)+12x | | (1)/(12)+(3)/(8)y=(5)/(12)+(5)/(8)y | | 16=x+8 | | 4x^3+x^2-64x-16=0 | | S^2+12sf+27f^2= | | -5-7x=65 | | -9=-11 | | -5x^2+90x=0 | | 2s^2-24s+72= | | -13=5(1+4m)-19m | | 3(6x+2)=7x-5 | | 6-2x=-5x+3 | | 2.75x=3 | | 6a^2-19a+10= | | 2(4r+6)=(2)/(3)(12r+18) | | 5x+7=3+8x-8 | | -2+4x=-18 | | -5x^2+90x=225 | | x^2+x-16=0 | | 18=v(v-7) | | (x+2)-(3x-2)=x+3 | | 3(6x+2)=7-5 | | 18x+3y=12 | | 2(x-3)=6x+4 | | -3f=48 | | s/5-s/3=8 | | 11j-12= | | 26=-2(-3x-5)-2x | | .4b+6=10 |